-2(x+3)+5x-6=6-(x-3)+2x

Simple and best practice solution for -2(x+3)+5x-6=6-(x-3)+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(x+3)+5x-6=6-(x-3)+2x equation:


Simplifying
-2(x + 3) + 5x + -6 = 6 + -1(x + -3) + 2x

Reorder the terms:
-2(3 + x) + 5x + -6 = 6 + -1(x + -3) + 2x
(3 * -2 + x * -2) + 5x + -6 = 6 + -1(x + -3) + 2x
(-6 + -2x) + 5x + -6 = 6 + -1(x + -3) + 2x

Reorder the terms:
-6 + -6 + -2x + 5x = 6 + -1(x + -3) + 2x

Combine like terms: -6 + -6 = -12
-12 + -2x + 5x = 6 + -1(x + -3) + 2x

Combine like terms: -2x + 5x = 3x
-12 + 3x = 6 + -1(x + -3) + 2x

Reorder the terms:
-12 + 3x = 6 + -1(-3 + x) + 2x
-12 + 3x = 6 + (-3 * -1 + x * -1) + 2x
-12 + 3x = 6 + (3 + -1x) + 2x

Combine like terms: 6 + 3 = 9
-12 + 3x = 9 + -1x + 2x

Combine like terms: -1x + 2x = 1x
-12 + 3x = 9 + 1x

Solving
-12 + 3x = 9 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-12 + 3x + -1x = 9 + 1x + -1x

Combine like terms: 3x + -1x = 2x
-12 + 2x = 9 + 1x + -1x

Combine like terms: 1x + -1x = 0
-12 + 2x = 9 + 0
-12 + 2x = 9

Add '12' to each side of the equation.
-12 + 12 + 2x = 9 + 12

Combine like terms: -12 + 12 = 0
0 + 2x = 9 + 12
2x = 9 + 12

Combine like terms: 9 + 12 = 21
2x = 21

Divide each side by '2'.
x = 10.5

Simplifying
x = 10.5

See similar equations:

| 2*y=9-3*y-4 | | 689=p-41 | | 27=n+y | | 3w+7(w+8)=36 | | 4(2x-2)+10=-38 | | 9(2+2y)= | | 3-3*3+2= | | -6=5(y-6)+7y | | 3(4x-2)=-4x+26 | | x+3yi=6i | | 3w-15=2w-10 | | 2u+6(u+5)=14 | | 9w-31=6w-18 | | 3w-15=2w+10 | | 2(5x+1)-7=4x+7 | | 32x=-967 | | -11+6=-11 | | x^2+14x-23=0 | | 35x^5-2x=0 | | 144+8=78 | | (17-3)=5(17)+5(-3) | | -4x=35.3 | | y=4x+34 | | 13.7x=-523 | | 132=.15x | | 10-z=-8 | | 8.31x+58.17=116.34 | | 3x-2-x-1=x+1 | | 42x-14y=28 | | -5x^2-20=-20x | | 6x-2x-7=2x-2x+5 | | 10a=2 |

Equations solver categories